1997
DOI: 10.1046/j.1365-2958.1997.4801846.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐dependent reciprocal transcriptional regulation of methane monooxygenase genes in Methylococcus capsulatus and Methylosinus trichosporium

Abstract: SummaryThe methanotrophic bacteria Methylococcus capsulatus (Bath) and Methylosinus trichosporium OB3b convert methane to methanol using the enzyme, methane monooxygenase (MMO). These bacteria are able to express two distinct MMOs: a cytoplasmic or soluble form (sMMO) and a membrane-bound or particulate form (pMMO). Differential expression of sMMO and pMMO is regulated by the amount of copper ions available to the cells; sMMO is expressed at low copper-biomass ratios, whereas pMMO is expressed at high copper-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
138
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 30 publications
6
138
0
2
Order By: Relevance
“…This indicates it is unlikely any of the known alternate MOs in strain NBB4 are essential for initiating growth on alkanes, since there is no precedent for ATU inhibition of an iron-containing MO, or a copper requirement for iron MO-mediated growth on hydrocarbons. Experimental data showing a lack of ATU sensitivity exist for the sMMO of Methylosinus trichosporium and the butane monooxygenase of Thauera butanivorans (Nielsen et al, 1997;Hamamura et al, 2001), and in strain NBB4, SDIMO-mediated growth on ethene was unaffected by ATU. Further indirect support for lack of involvement of iron-MOs comes from the apparent absence of any iron MO from the proteome of NBB4 cells grown on C 2 -C 4 alkanes .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates it is unlikely any of the known alternate MOs in strain NBB4 are essential for initiating growth on alkanes, since there is no precedent for ATU inhibition of an iron-containing MO, or a copper requirement for iron MO-mediated growth on hydrocarbons. Experimental data showing a lack of ATU sensitivity exist for the sMMO of Methylosinus trichosporium and the butane monooxygenase of Thauera butanivorans (Nielsen et al, 1997;Hamamura et al, 2001), and in strain NBB4, SDIMO-mediated growth on ethene was unaffected by ATU. Further indirect support for lack of involvement of iron-MOs comes from the apparent absence of any iron MO from the proteome of NBB4 cells grown on C 2 -C 4 alkanes .…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence argue that the eight iron-containing enzymes are not involved in initiating growth on gaseous hydrocarbons. A copper requirement is a distinctive feature of the CuMMO-dependent autotrophic ammonia oxidizers and methanotrophs (Nielsen et al, 1997;Lieberman and Rosenzweig, 2005), therefore we tested the effect of copper-free media vs standard media (0.8 mM Cu 2 þ ) on the growth substrate range of strain NBB4. In copper-free media, growth on gaseous alkanes (ethane, propane and butane) was strongly limited, but growth on other carbon sources, including alkenes, organic acids and glucose, was unaffected (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…However, mutants are not available in the other a m o genes. A 3.3 kb transcript covering pmoA, pmoB and p m o C as well as smaller transcripts are detectable in Methylococcus capsulatus Bath and Methylosinus trichosporium OB3b expressing pMMO, but it is not known which of the sets of genes is responsible for these transcripts (Nielsen et al, 1997). Likewise, analogous transcripts have been detected in nitrifying bacteria, and it has been shown that the a m o A mutant showing slower growth also has decreased amounts of these transcripts Sayavedra-Soto et al, 1998).…”
Section: Introductionmentioning
confidence: 88%
“…In addition, a gene encoding the 23 kDa subunit (pmoC1) has been shown to be present upstream of pmoAl (Nguyen et al, 1996). pmoA1 and pmoBl showed substantial similarity to genes encoding the analogous subunits of a related enzyme, ammonia monooxygenase (Semrau et al, 1995), which are also present in multiple copies in nitrifying bacteria (McTavish et af., 1993;Norton et al, 1996). In the nitrifiers, the genes are also organized in a cluster in the order amoCAB with an additional, single copy of amoC Sayavedra-Soto et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation